MODELLING OF MODES OF A THREE-PHASE CHAIN WITH CROSS-SECTION ASYMMETRY - Gennadij P. Karabashev (Открытое образование (Москва))
In article process of modelling of modes of electric chains in program LabVIEW environment is shown. The modelling purpose is working out of the computer program (device) as for an illustration of electric processes in a three-phase chain at various asymmetrical modes in educational process of internal and correspondence (remote) formation, and for defi nition of parametres of these modes in the practical purposes (calculation К.З).